Academic performance and peer relations among rural‐to‐urban migrant children in Beijing: Do social identity and self‐efficacy matter?. Issue 3 (10th July 2019) - Wang, Yixuan; Pei, Fei; Zhai, Fuhua; Gao, Qin
Abstract: Due to the household registration system, millions of rural‐to‐urban migrant children in China are ineligible to receive urban social welfare benefits. These children potentially suffer from the evolving awareness of their perceived inferior social identity and experiences of inequalities at an early stage of life. This study examined whether self‐perceived social identity is related to academic performance and peer relations among rural‐to‐urban migrant children in Beijing. Data were collected from 136 children during 2013 and 2014 in three schools for migrant children in Beijing. Path analysis showed that children who identified as a Beijinger, compared with those who self‐identified with their rural hometown, had better self‐efficacy, which in turn was associated with better academic performance and better peer relations. Enlightened by Western theories, these findings suggest that migrant children's performance in school could be enhanced by cultivating positive perceptions of their social identity through teachers' practice and community‐ and policy‐level social support.